Survei Kreativitas Guru PJOK SMA Se-Kabupaten Bantul Dalam Pembelajaran Bola Voli di Masa Covid 19 - Akas Nandang Prahara (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
Creativity is the ability to create something new. Its form is human action through a creative process that takes place in the minds of people or a group, creative products are created. The products themselves vary widely. The spread of which is spreading so fast in Indonesia has disrupted the education sector in Indonesia, thus requiring students not to be able to continue their study activities as they should at school. The government also recommends that learning be carried out, through online media (in the network). This study aims to determine the level of creativity of physical education teachers in Bantul Regency in learning volleyball during the Covid-19 pandemic. The population in this study were 42 high school physical education teachers in Bantul Regency, while the sample used total sampling amounted to 42 respondents. Data collection techniques using questionnaires or google forms. The data analysis techniqueused in this study uses a quantitative descriptive analysis technique with a percentage (%). The results of this study showed that the creation of physical education teachers in Bantul Regency in learning volleyball during the Covid-19 pandemic was relatively high with a total of 21 teachers (50%), this number was the largest frequency of the overall results of taking the 42 data that had been carried out.